Advanced Information Security and Assurance: A Literature Review of Zero Trust Architecture, Artificial Intelligence, and Cybersecurity Resilience (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The quick uptake of cloud computing, artificial intelligence (AI), Internet of Things (IoT), and hybrid workplace solutions has changed the cybersecurity needs in a way that renders the traditional notion of perimeter defense inefficient in addressing sophisticated attack scenarios such as ransomware, insider threats, and advanced persistent threats (APTs). This literature review analyzes advancements in the field of Advanced Information Security and Assurance from 2016 to 2026.Key advancements include NIST SP 800-207 published in 2020, widespread use of Zero Trust Architecture (ZTA), and incorporation of AI into security analytics. The reviewed sources show that Zero Trust drastically minimizes attack surfaces using continuous authentication, least-privilege access, and microsegmentation. Also, AI is beneficial in improving threat detection through predictive analytics, behavioral anomalies detection, and automation of the incident response process.On the other hand, AI also poses emerging risks such as adversarial machine learning, automated API reconnaissance, AI phishing scams, and intelligent malware. Additionally, cyber resilience, explainable AI, and adaptive governance are the identified research areas important for protecting future digital infrastructures. While significant advances have been made, there are still many challenges related to complexity, interoperability, staffing shortage, privacy, and governance.